Prevention of recurrent respiratory infections - Elena Chiappini; Francesca Santamaria; Gian Luigi Marseglia; Paola Marchisio; Luisa Galli; Renato Cutrera; Maurizio de Martino; Sara Antonini; Paolo Becherucci; Paolo Biasci; Barbara Bortone; Sergio Bottero; et al. (BMC, 2021)
Abstract Recurrent respiratory infections (RRIs) are a common clinical condition in children, in fact about 25% of children under 1 year and 6% of children during the first 6 years of life have RRIs. In most cases, infections occur with mild clinical manifestations and the frequency of episodes tends to decrease over time with a complete resolution by 12 years of age. However, RRIs significantly reduce child and family quality of life and lead to significant medical and social costs. Despite the importance of this condition, there is currently no agreed definition of the term RRIs in the literature, especially concerning the frequency and type of infectious episodes to be considered. The aim of this consensus document is to propose an updated definition and provide recommendations with the intent of guiding the physician in the complex process of diagnosis, management and prevention of RRIs.